An Overview on Vascular Calcification in Chronic Kidney Disease - Salah Ibrahim, Mostafa Mahmoud; Mohammed, Ezzat Mostafa; Abdel Rahman, Hossam Eldin Mansour; Abdel-Rahaman , Abeer Abd Alla Fikry; Shaker , George Emad; Yousef , Amr Galal Ibrahim; Ahmed Ezzat Mostafa, Malak Emad Samy; Taha Morsi, Fatima Al Taher (Journal of Neonatal Surgery, 2025)
Vascular calcification (VC) is a prevalent and severe complication in chronic kidney disease (CKD), contributing significantly to cardiovascular morbidity and mortality. Its pathogenesis involves disordered mineral metabolism, chronic inflammation, and vascular smooth muscle cell trans differentiation.